The stress of travel - Waterhouse, J.; Reilly, T.; Edwards, B. (Journal of Sports Sciences, 2004)
International travel is an essential part of the life of elite athletes, both for competition and training. It is also becoming increasingly common among recreational sportspersons. Long-distance travel is associated with a group of transient negative effects, collectively referred to as 'travel fatigue', which result from anxiety about the journey, the change to an individual's daily routine, and dehydration due to time spent in the dry air of the aircraft cabin. Travel fatigue lasts for only a day or so, but for those who fly across several time zones, there are also the longer-lasting difficulties associated with 'jet lag'. The problems of jet lag can last for over a week if the flight crosses 10 time zones or more, and they can reduce performance and the motivation to train effectively. Knowledge of the properties of the body clock enables the cause of the difficulties to be understood (an unadjusted body clock), and forms the basis of using light in the new time zone to promote adjustment of the body clock. Sleep loss and its effects are important components of jet lag, and attempts to promote sleep by the use of melatonin and other hypnotics are also relevant. Sleep loss is also found in those who undertake challenges that involve long periods where the normal consolidated sleep of 8 h length is not possible. Advice on sleep regimens in such circumstances is given.